posted by .

1. Use the Taylor series to calculate the limit.

Problem: limit as x approaches 0 is equal to (1-cos(x))/(1+x-e^x).

I did the problem out but I need help in seeing if its correct.

limit as x approaches 0 is equal to (1-cos(x))/(1+x-e^x)= (1-(1-x^2/2+x^4/4!-...))/(1+x-(1+x+x^2/2+x^3/3!+x^4/4!+...)=(x^2-x^4/4!+...)/(-x^2/2-x^3/3!-x^4/4!-...)=-11/17

  • Calculus -

    It is wrong. You also need to use the "Big O" notation. One denotes by
    O(x^n) a term that for x to zero behaves as a constant times x^n. More rigorously, we say that some term T(x) is O(x^n) if and only if there exists a p and C such that

    |T(x)| <= C |x^n| for all |x| < p

    THen we can proceed as follows. We have:

    1-cos(x) = 1/2 x^2 + O(x^4)

    1 +x-exp(x) = -1/2 x^2 + O(x^3)

    [1-cos(x)]/[1+x-exp(x)] =

    -[1+O(x^2)]/[1+O(x)] =

    -[1+O(x^2)][1+O(x)] =

    -1 + O(x)

    Limit of x to zero is then -1, because the O(x) tends to zero as it is less than x for x sufficiently close to zero.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    How to solve for delta using trig functions?
  2. calculus help again

    if f'(x)=cos x and g'(x)=1 for all x, and if f(0)=g(0)=0, then the limit x--->0 fo function f(x)/g(x)= okay, so f(x)=sinx g(x)=x and the f(0)=g(0)=0 is also satisfied and equals o. so the limit x-->o of sinx/x= is the answer …
  3. Calc

    I have a test soon.. and I really need to know how to do this problem.. please help!!! lim as x-->0 sin^2(x)/tan(x^2) the answer is 1, but I have no clue how to get that! Use series expansions. Look up Taylor expansion on google …
  4. Differential Calculus

    use the rule that says limit of (e^h - 1)/h = 1 as h approaches 0 to show that the limit of [ln(x+h) -lnx]/h as h approaches 0 = 1/x, where x>0
  5. Calculus

    Could someone please help me with these questions;I was having trouble with these four questions. Evaluate each limit, if it exists, using any appropriate technique. 1.) The limit as u approaches 4; u^2-16/u^3-64 2.) The limit as x …
  6. calculus

    I'm not sure how to find the limit of this problem :S limit as x -> 0+ (cos(x))^(1/x^2)
  7. calculus verify answer

    Evaluate the limit: Limit as x approaches 6 from the right: Sq.root of (x - 6). I know the limit is 0, but how do I show this?
  8. Calculus

    What is the limit of this function as x approaches 0?
  9. Calculus

    1. Evaluate the function at the given numbers (correct to six decimals places). Use the results to guess the value of the limit,or explain why it does not exist. F(t)=( t^(1/3) - 1)/(t^(1/2) - 1) ; t= 1.5,1.2,1.1,1.01,1.001; The limit …
  10. calculus

    Use series to evaluate the limit. limit as x approach 0 [1-cos(5x)]/[1+5x-e^(5x)]

More Similar Questions